East German unemployment from a macroeconomic perspective - Jens Rubart; Willi Semmler (Technische Universität Darmstadt, Department of Law and Economics, 2007)
When reviewing the literature concerning the development of the Eastern German economy, a too rigid labor market and its respective institutions are considered as the main source of the persistent high unemployment rates and the slow economic performance. However, when important macroeconomic variables are considered a significant decline in investment in new technologies is observed. In addition, we find evidences that the decline in investment might be affected by the steady migration of young and skilled workers to West Germany. The decline in the proportion of skilled workers induces firms not to invest in Eastern Germany which leads to a general decline in job creating activities irrespective rigid labor markets and generous social benefits. In the recent paper we employ a rather standard Dynamic General Equilibrium model in order to study the effects of a decline in the proportion of skilled workers as well as the impacts of increasing benefit payments. Furthermore, we assume equilibrium unemployment due to search and matching frictions on the labor market. This approach enables us further to consider job creating activities of the firms. We show that an emigration shock of skilled- workers is capable to reproduce the findings for the decline in economic activity. This effect is strengthened by assuming generous social benefit payments.
Keywords: E20; J21; J24; J64; 330; DSGE Model; Heterogenous Labor; Skill Biased Technological Change; Search Unemployment; Employment Protection; Minimum Wages; Dynamisches Gleichgewicht; Technischer Fortschritt; Humankapital; Arbeitnehmerschutz; Mindestlohn; Beschäftigungseffekt; Neue Bundesländer